Chemical Hydrolysis-Gamma Irradiation Processes for Cellulose Nanofibers Isolation from Rice Straw - Swantomo, Deni; Basuki, Kris Tri; Haryanto, Haryanto; Saefurrochman, Saefurrochman; Wongsawaeng, Doonyapong (International Journal of Integrated Engineering, 2024)
Utilization of agriculture biomass waste into high value product is still potential to develop. In this study, cellulose nanofibers (CNF) as valuable materials were isolated from rice straw. Sodium hydroxide pulping and hydrogen peroxide bleaching were conducted as cellulose pretreatment. The CNF was prepared using 1 M hydrochloric acid hydrolysis followed gamma irradiation with various radiation doses, i.e. 40, 60, 80, 100 and 120 kGy. Compositions of ?–cellulose and water retention of each stage processes increased inversely with hemicellulose, lignin and degrees of polymerization which had been strengthened by Fourier transform infrared spectroscopy (FTIR) spectra. X-ray Diffraction (XRD) analysis revealed that crystallinity index was more intense than rice straw, i.e. 80.85 %. Particle Size Analyzer (PSA) studies described the isolation process of CNF succeed with the smallest size 77.8 nm. The CNF functional groups of hydrophilic both hydroxyl and carboxylate slightly diminished with increasing of radiation doses followed water retention reducing, however the crystallinity had not changed significantly. Increasing radiation doses also could improve the thermal stability with the highest Tg 153.1 0C therefore the obtained CNF could be used as suitable nanocomposite.